Evaluations of turonian limestone formation exposed at nigercem-quarry, Nkalagu, southeastern Nigeria: a geochemical approach. (2009)
" A geochemical study of Nkalagu limestone of the Lower Benue Trough as exposed at Nigeria Cement Company (NIGERCEM) was carried out. The study aims at the determination of major oxides and trace elements of the limestone exposed in the quarry using X–Ray Fluorescence Spectrophotometer (XRF) and Atomic Absorption Spectrophotometer (AAS) respectively as well as reconstructing the depositional history of the deposit. Petrographic study was also done to enhance the determination of biogenic contents of the deposit. Results of fifteen (15) samples collected for analysis put the range major elements as follow: CaO (46.56 – 54.15%), SiO2 (3.12 – 10.04%), Fe2O3 (0.23 – 1.37%), MgO and Al2O3 (0.72 – 1.27%) and (0.65 – 1.90%) respectively. Also, the trace elements contents expressed in ppm were found to be 1653 – 3306 for Fe, 76 – 1543 for Mn, 600 – 1035 for Sn and 4.5 – 53 for Zn. Interpretation of these results suggest a shallow marine possibly an off – shelf depositional model for the formation. "